Review of Filter-Based Image Denoising Methods - Zhao, Xiaolong; Zhang, Mingchuan (International Journal of Computer Science and Information Technology, 2024)
Image denoising is one of the fundamental tasks in the field of digital image processing. In tasks such as object detection, the effectiveness of image denoising plays a crucial role in the accuracy of the detection results. As image acquisition devices and technologies continue to advance, various types of noise, such as Gaussian noise and salt-and-pepper noise, are commonly present in images. These types of noise have a detrimental impact on the quality and visual fidelity of the images. Consequently, the research and application of image denoising techniques hold significant importance in improving image quality, enhancing fine details, and accurately analyzing image content. Among the myriad of image denoising methods, filter-based approaches have garnered notable attention due to their simplicity, efficiency, and ease of implementation. This paper aims to provide a comprehensive overview and reference for researchers in the field by reviewing the research progress and potential breakthrough directions of filter-based image denoising methods.